The RESPECT Study for consensus on global bereavement care after stillbirth. Issue 2 (26th February 2020) - Shakespeare, Clare; Merriel, Abi; Bakhbakhi, Danya; Blencowe, Hannah; Boyle, Frances M.; Flenady, Vicki; Gold, Katherine; Horey, Dell; Lynch, Mary; Mills, Tracey A.; Murphy, Margaret M.; Storey, Claire; et al.
Abstract: Objective: To develop global consensus on a set of evidence‐based core principles for bereavement care after stillbirth. Methods: A modified policy‐Delphi methodology was used to consult international stakeholders and healthcare workers with experience in stillbirth between September 2017 and October 2018. Five sequential rounds involved two expert stakeholder meetings and three internet‐based surveys, including a global internet‐based survey targeted at healthcare workers in a wide range of settings. Results: Initially, 23 expert stakeholders considered 43 evidence‐based themes derived from systematic reviews, identifying 10 core principles. The global survey received 236 responses from participants in 26 countries, after which nine principles met a priori criteria for inclusion. The final stakeholder meeting and internet‐based survey of all participants confirmed consensus on eight core principles. Highest quality bereavement care should be enabled through training of healthcare staff to reduce stigma and establish respectful care, including acknowledgement and support for grief responses, and provision for physical and psychologic needs. Women and families should be supported to make informed choices, including those concerning their future reproductive health. Conclusion: Consensus was established for eight principles for stillbirth bereavement care. Further work should explore implementation and involve the voices of women and families globally. Abstract : A modified policy‐Delphi process has been used to establish global consensus on eight principles for bereavement care after stillbirth.